2001
DOI: 10.1038/ncb1001-897
|View full text |Cite
|
Sign up to set email alerts
|

N-WASP deficiency reveals distinct pathways for cell surface projections and microbial actin-based motility

Abstract: The Wiskott-Aldrich syndrome protein (WASP) family of molecules integrates upstream signalling events with changes in the actin cytoskeleton. N-WASP has been implicated both in the formation of cell-surface projections (filopodia) required for cell movement and in the actin-based motility of intracellular pathogens. To examine N-WASP function we have used homologous recombination to inactivate the gene encoding murine N-WASP. Whereas N-WASP-deficient embryos survive beyond gastrulation and initiate organogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
287
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(314 citation statements)
references
References 50 publications
24
287
2
1
Order By: Relevance
“…1D). Gross examination of E8.0-E11.0 embryos revealed marked developmental delay with prominent neural tube and cardiac abnormalities similar to those observed for N-Waspnull embryos (33). As early as E8.5, Abi-null embryos exhibited developmental delay (smaller size, some unturned embryos).…”
Section: Resultssupporting
confidence: 63%
“…1D). Gross examination of E8.0-E11.0 embryos revealed marked developmental delay with prominent neural tube and cardiac abnormalities similar to those observed for N-Waspnull embryos (33). As early as E8.5, Abi-null embryos exhibited developmental delay (smaller size, some unturned embryos).…”
Section: Resultssupporting
confidence: 63%
“…It has been shown that human platelet extracts supported Shigella actin-based motility as added N-WASP in vitro (Egile et al, 1999). Recent reports using N-WASP-deficient mouse embryonic fibroblasts (Lommel et al, 2001;Snapper et al, 2001) confirmed our previous work indicating that N-WASP is required for Shigella motility in mammalian cells (Suzuki et al, 1998). However, the role of the WASP family proteins in Shigella spreading in infected cells such as epithelial cells or macrophages is poorly understood.…”
supporting
confidence: 58%
“…In animal cells, the two major classes of Arp2͞3 activators are the WASP proteins and the Wave proteins. WASP proteins are dispensable for the formation of lamellipodia (2,3), whereas Wave proteins have emerged as a critical regulator of this structure. In fact, Wave proteins are localized at the tip of the protruding lamellipodium and delocalized whenever this structure retracts (4); genetic inactivation of the ubiquitously expressed Wave-2 gene causes defects in the formation of lamellipodia (5,6).…”
mentioning
confidence: 99%